Single-Cell RNA-Seq Analysis Maps Development of Human Germline Cells and Gonadal Niche Interactions - Li, Li; Dong, Ji; Yan, Liying; Yong, Jun; Liu, Xixi; Hu, Yuqiong; Fan, Xiaoying; Wu, Xinglong; Guo, Hongshan; Wang, Xiaoye; Zhu, Xiaohui; Li, Rong; et al. (Cell stem cell, 2017)
Human fetal germ cells (FGCs) are precursors to sperm and eggs and are crucial for maintenance of the species. However, the developmental trajectories and heterogeneity of human FGCs remain largely unknown. Here we performed single-cell RNA-seq analysis of over 2,000 FGCs and their gonadal niche cells in female and male human embryos spanning several developmental stages. We found that female FGCs undergo four distinct sequential phases characterized by mitosis, retinoic acid signaling, meiotic prophase, and oogenesis. Male FGCs develop through stages of migration, mitosis, and cell-cycle arrest. Individual embryos of both sexes simultaneously contain several subpopulations, highlighting the asynchronous and heterogeneous nature of FGC development. Moreover, we observed reciprocal signaling interactions between FGCs and their gonadal niche cells, including activation of the bone morphogenic protein (BMP) and Notch signaling pathways. Our work provides key insights into the crucial features of human FGCs during their highly ordered mitotic, meiotic, and gametogenetic processes in vivo. [Display omitted] •RNA sequencing of 2,167 single FGCs identifies multiple stages in individual embryos•Transcriptome landscapes decode TF networks underlying distinct developmental stages•Reciprocal BMP and Notch signaling occurs between FGCs and their niche cells•Female embryos contain four stages of FGCs, even in later developmental stages Li et al. interrogate the transcriptomes of over 2,000 fetal germ cells (FGCs) and their gonadal niche cells from male and female human embryos using single-cell RNA-seq analysis. They provide insights into the developmental trajectories and heterogeneity in FGCs over a wide range of developmental stages.